Management of a sales force - Stanton, William J.; Spiro, Rosann L.; Stanton, William J. (Boston : Irwin, 1999)
This text covers the concepts and applies the theories associated with managing a sales force. It emphasizes relationship selling and the use of team-selling.
Revised edition of: Management of the sales force. 8th ed. c1991.
Includes bibliographical references and index.
Keywords: Sales management